Pengembangan Media Ensiklopedia Berbasis Flip PDF Professional Sebagai Sumber Belajar Biologi (Model Pengembangan ADDIE pada Materi Keanekaragaman Spesies Gastropoda di Pantai Kalala) - Silvani Dama Ata Hawu; Vidriana Oktoviana Bano; Yohana Ndjoeroemana (Pustaka Digital Indonesia, 2025)
The urgency of this research lies in the need to provide an interactive, easily accessible, and contextual digital learning media to overcome the limitations of printed materials at SMA Negeri 1 Wulla Waijelu, thereby making biology learning particularly on the biodiversity of Gastropods at Kalala Beach more effective and engaging. This study aims to analyze problems, design media, and develop Flip Pdf Professional-based Encyclopedia media on the Diversity of Gastropod Species. The method used is Research and Development (R&D) using the ADDIE model. The development stages include Analysis, Design, Development, Implementation, and Evaluation. In this study, only three stages were conducted: Analysis, Design, and Development. Data collection techniques used are Observation, Interviews, Questionnaires, and Documentation. Data analysis techniques are carried out through the analysis of validation results from media, material, and language experts. The development result is Flip Pdf Professional-based Encyclopedia media. The validation results from the material expert obtained a percentage of 81%, while validation from two material experts obtained an average percentage of 85%. Furthermore, validation results from two language experts produced an average percentage of 89%. Thus obtaining an overall average percentage from all validators of 85%, which indicates a very feasible criterion. Based on the experts' results, it can be concluded that the development and feasibility of an Encyclopedia based on Flip Pdf Professional can be further developed.